A GLOBAL SEARCH FOR UNIVERSAL MODELS OF EDUCATION AND TRAINING IN ELECTRONIC RECORDS MANAGEMENT - Johare, Rusnah (Malaysian Journal of Library and Information Science, 2007)
In developed countries, education and training for records practitioners and other key players on electronic records management (ERM) are provided by the universities, professional organisations, private consultants and individual archival institutions, or through collaboration between the various organisations. However, evidence from the review of literature suggests that in many countries especially those in Asia, the present situation is characterised by a lack of local expertise, experience and facilities. As a result, records practitioners are sent to developed countries to acquire knowledge and skills on ERM, or foreign experts are brought in to conduct in-service training for government record keepers. According to the literature, these issues have already been addressed in the UK and Europe where education and training programmes on ERM have been developed to provide the key players with the required knowledge and skills. Pursuance to this development, an international survey was conducted to identify universal models of education and training programmes in ERM. This article reports and discusses the findings of the survey questionnaire of the national archival institutions and related professional associations world wide for administrators, archivists, information managers, IT specialists and records managers.